Sentence Conjunctions in Surat Youssef: Examples and Quotes - Hamid, Fatima Mohammed Taher (Al-Adab Journal, 2022)
This research aims to study conjunctions in Surat Youssef. The research plan was as follows:The introduction included the research plan, questions, research limits, reasons for choosing it and previous studiesThe preface included the lexical and contextual definition of conjunction and conjunctions in the Quranic studiesThe research topics included: Three topics, topic one included:The conjunctions in the views of ancient and modern scholarsThe conjunctions in the views of modern scholarsTopic two included sentences as follows:the lexical and contextual definition of sentencestypes of sentencesTopic three included types of conjunctions as follows:Sentences conjunctionsConjunctions in Surat YoussefThe conclusion included the most important findings, sources and references. The research concluded the following findingsSentence conjunctions have direct role in linking the text and its contribute to its harmony and have an impact on revealing the Quranic verses meaningsPronouns have apparent impact on the linking of sentences as they clarify the meaning and lead to the text being shorten and briefConjunctions connects the words together, nouns to nouns, verbs to verbs, sentence to sentence, and make the text as a connected unit and harmonious.Interrogatives connect parts of speech and alert the recipient's mind to the intended meaning.The Chapters of the Noble Qur’an are fit, in a way that achieves the objective unity in it.The conjunctions evident in Surat Yusuf, for this is the surah that was not repeated in the Qur’an, rather, it came completely in one surah.